Comparison of External and Internal Injury in Cases of Fatal Blunt Trauma Head Injury Autopsied at Tertiary Care Centre in Eastern Nepal - Sah, Bikash; Yadav, Bishwanath; Jha, Shivendra (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Blunt trauma is more likely to be missed because clinical signs are less obvious in many regions of the body. This study was done with an objective to compare external and internal injuries of autopsy cases with fatal blunt trauma head injuries. Materials & Methods: This was a hospital based, cross sectional and analytical study done on the autopsy cases at B. P. Koirala Institute of Health Sciences, Dharan, Nepal (tertiary hospital in eastern Nepal) from 13th April 2012 to 13th April 2013 with Head injuries by blunt trauma with or without concomitant non-head injuries. The decomposed bodies and the bodies where cause of trauma could not be differentiated were excluded. Postmortem examination was conducted on all the cases and the injuries present on all the body parts were noted. Abbreviated Injury Scale (AIS) score was given for each injury. Appropriate statistical tool was used to compare the AIS scores of external and internal injuries. The test of significance was fixed at p < 0.01. Results: The correlation of scalp injuries with that of skull fracture, intracranial hemorrhage, cerebral injury and overall internal head injury were 0.591, 0.772, 0.439 and 0.600 respectively and all these correlations were statistically significant whereas the correlation between concomitant external and internal non-head injuries is -0.092 which is statistically not significant. Conclusion: This study has shown a statistically significant positive correlation between external and internal blunt trauma head injuries but there is no statistically significant correlation between concomitant external and internal non-head injuries.